PENERAPAN INKUIRI TERBIMBING DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS V PADA MATERI DAUR AIR - Nurhayati, Ai Ratna; Jayadinata, Asep Kurnia; Sujana, Atep (Jurnal Pena Ilmiah, 2017)
Classroom action research using guided inquiry is motivated by problems in learning process and critical thinking ability of class V students. The purpose of this research is to know and explain the process of learning and improvement of critical thinking skills of students using guided self in water cycle materials. Guided inquiry has five stages of learning. The critical thinking skills of the students in this research are 5 indicators: simple explanation, building basic skills, concluding, giving further explanation, and managing strategy and tactics. The design of classroom action research in this study is a design developed by Kemmis Taggart consisting of three cycles. Participants of this research are students of grade V in Elementary School of Cimalaka II. The findings of this study show students' critical thinking skills have improved in each cycle. The mean score of the student's test result is 57,5 on cycle I, 70,4 on cycle II and 80,4 in cycle III. The conclusion of this research is the learning by using guided inquiry to improve the students' critical thinking skill.